Kurasi Digital Sastra Siber untuk Author dan Digital Publisher - Indrawati, Tri; Tchaikovsky, Virtu Ozo Fable; Patricia, Aretha Hanny (Khazanah: Jurnal Pengembangan Kearsipan, 2024)
The advancement of digital technology has resulted in the rise of diverse manifestations of cyber literature. Cyber literature has different characteristics from conventional literature, so it requires a special approach to sustainability. Digital curation for cyber literature is important to ensure its sustainability as a form of expression. This research aims to explore the digital curation of cyber literature for authors and digital publishers. This research uses qualitative methods with case studies and a literature review. Data were obtained through interviews with authors and digital publishers on the KaryaKarsa platform as well as academic literature data that discusses cyber literature. The results of the study show that authors and digital publishers have curated cyber literary works in different ways. Authors generally store their works on physical storage devices, such as laptop hard drives and Onedrive. Digital publishers store their works on digital publishing platforms, such as KaryaKarsa cloud storage. Authors need to maintain their original works, by doing regular back ups and utilizing cloud storage. Storage can also be done through digital publishing to maintain future works.